2013
DOI: 10.1364/oe.21.015382
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ablation thresholds of optical materials using 1-µm-focusing beam at hard X-ray free electron laser

Abstract: We evaluated the ablation thresholds of optical materials by using hard X-ray free electron laser. A 1-µm-focused beam with 10-keV of photon energy from SPring-8 Angstrom Compact free electron LAser (SACLA) was irradiated onto silicon and SiO2 substrates, as well as the platinum and rhodium thin films on these substrates, which are widely used for optical materials such as X-ray mirrors. We designed and installed a dedicated experimental chamber for the irradiation experiments. For the silicon substrate irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…We also note that the estimated beam size and shape were consistent with those determined by normal incidence measurements taken on lead(II) iodide 9 and on silicon oxide. 10 It is of note that the fluence damage thresholds are far higher than the values obtained for normal incidence measurements or measurements conducted at lower photon energies. 11,12 This is due to a significant fraction of the pulse energy being reflected by the mirror coatings and not absorbed into the material.…”
mentioning
confidence: 82%
“…We also note that the estimated beam size and shape were consistent with those determined by normal incidence measurements taken on lead(II) iodide 9 and on silicon oxide. 10 It is of note that the fluence damage thresholds are far higher than the values obtained for normal incidence measurements or measurements conducted at lower photon energies. 11,12 This is due to a significant fraction of the pulse energy being reflected by the mirror coatings and not absorbed into the material.…”
mentioning
confidence: 82%
“…In the high fluence regime, the studied system considerably deviates from the ground state and our model anticipates water molecules with far more than one valence hole. Effects like Coulomb explosion strongly affecting the geometric structure have been observed for heavier elements, e.g., silicon [31][32][33][34][35] in a similar fluence regime and have been predicted and observed for lighter elements at significantly higher fluences [36,37]. Although a detailed description of the connected effects on the electronic structure and nuclear motions is beyond the scope of this Letter, the created valence holes can still reabsorb x-ray emission at these high fluences.…”
Section: -3mentioning
confidence: 59%
“…Instead, it was estimated to be 410 mJ/cm 2 , from experimental values obtained for irradiations at the wavelength of 32.5 nm [5,9] and 0.124 nm (10 keV photon energy) [12,13] and theoretical predictions [20].…”
Section: Methodsmentioning
confidence: 99%
“…For silicon, phase transition mechanisms induced with a single femtosecond and monochromatic pulse of wavelength in the range of XUV and X-ray were studied previously, mainly with an angle of incidence close to surface normal. Bulk crystals [5,[7][8][9][10][11][12][13] together with a-Si layers in Si/C and Mo/Si multilayer systems [14,15] have been examined. These measurements have shown that single shot structural modifications are caused by melting.…”
Section: Introductionmentioning
confidence: 99%